The Effect of Tactical Exercises Based on the Sensory Representational System on Students' Learning of Some Basic Soccer Skills (Damu Journal of Sport Sciences, 2025)
The sensory representational system is one of the most recent educational methods that relies on classifying learners according to their different sensory patterns, including visual, auditory, and kinesthetic. The sensory pattern is considered one of the most influential patterns in sports learning and is an essential element that improves the ability to execute movements smoothly and accurately. Based on this importance, this research seeks to develop tactical exercises based on the sensory representational system. Many traditional educational programs may not take into account individual differences in learners' sensory representational patterns, which may lead to failure to achieve maximum benefit. Hence, the problem of the study arises in the following question: Do tactical educational exercises based on the sensory representational system have an impact on learning some basic soccer skills? The experimental approach was used on a sample of physical education college students with a sensory preference. The study employed tactical exercises based on the sensory representational system to teach the students some basic soccer skills. The results showed significant differences between the pre- and post-tests in skills. Based on these results, it can be said that tactical exercises based on the sensory system have proven effective in developing soccer skills, making them a powerful training tool that can be utilized in learner development programs.